1998
DOI: 10.1093/geront/38.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Utilization, Hospital Admissions, and Physician Visits Among Elderly African American Persons

Abstract: This study uses a theoretical model of health services utilization to examine (a) emergency department utilization, (b) hospital admissions, and (c) office-based physician visits among a sample of 998 low-income elderly African American persons. Poisson Regression analysis was used to estimate the parameters specified in the Andersen behavioral model. Some of the more interesting results include the following: (a) a greater frequency of emergency room visits among respondents with a lower level of accessibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
94
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 27 publications
2
94
0
Order By: Relevance
“…Previous literature indicated that health needs factors such as morbidity and injury were primary predictors for emergency care (Bazargan et al, 1998;Cherpitel, 1999;Cowie, Cowie, Underwood, Revitt, & Field, 2001;Fan et al, 2011;Guilbert et al, 2011;McCusker et al, 2003;Merrick et al, 2011;Neighbors, Zywiak, Stout, & Hoffmann, 2005;Shah, Manish N., Rathouz, & Chin, 2001;Shah, S. M. & Cook, 2008;Siegal, Falck, Jichuan, Carlson, & Massimino, 2006;Simmons et al, 2008;Weber, Showstack, Hunt, Colby, & Callaham, 2005;Wolinsky et al, 2008). Other health needs factors such as patients' perceived severity of illness and patients' health status were also associated with demand for emergency care (Baker, D. W. et al, 1995;Bazargan et al, 1998;Bianco et al, 2003;Callen et al, 2008;Lee et al, 2000;Olsson & Hansagi, 2001;Selasawati et al, 2007).…”
Section: Health Needs Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous literature indicated that health needs factors such as morbidity and injury were primary predictors for emergency care (Bazargan et al, 1998;Cherpitel, 1999;Cowie, Cowie, Underwood, Revitt, & Field, 2001;Fan et al, 2011;Guilbert et al, 2011;McCusker et al, 2003;Merrick et al, 2011;Neighbors, Zywiak, Stout, & Hoffmann, 2005;Shah, Manish N., Rathouz, & Chin, 2001;Shah, S. M. & Cook, 2008;Siegal, Falck, Jichuan, Carlson, & Massimino, 2006;Simmons et al, 2008;Weber, Showstack, Hunt, Colby, & Callaham, 2005;Wolinsky et al, 2008). Other health needs factors such as patients' perceived severity of illness and patients' health status were also associated with demand for emergency care (Baker, D. W. et al, 1995;Bazargan et al, 1998;Bianco et al, 2003;Callen et al, 2008;Lee et al, 2000;Olsson & Hansagi, 2001;Selasawati et al, 2007).…”
Section: Health Needs Factorsmentioning
confidence: 99%
“…Individual health need factors, including morbidity, injury, and other health related factors, appear to be the primary predictors of ED utilization (Bazargan, Bazargan, & Baker, 1998;Cherpitel, 1999;McCusker, Karp, Cardin, Durand, & Morin, 2003;Wolinsky et al, 2008). A qualitative study (Ragin et al, 2005) of 1,579 patient interviews from 28 US hospitals found that medical necessity was the most frequently cited reason (95%) for patients attending EDs.…”
Section: Health Need Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout the decades of research utilizing the ABM, questions about whether the model sufficiently addresses psychosocial determinants of health, including culture (Andersen, 1995); social factors (Guendelman, 1991); psychological characteristics (Aday, 2001) and provider characteristics (Phillips, Morrison, Andersen, & Aday, 1998) have arisen. Some researchers have suggested that failure to add such factors to the ABM may contribute to the low predictive validity of ABM found in some previous studies (Bazargan & Bazargan, 1998;Keith & Jones, 1990;LaVeist & Keith, 1995 …”
Section: Alternate Theoretical Approachesmentioning
confidence: 99%